Estimation of Genetic Parameters and Trait Association in Wheat (Triticum aestivum L.) Genotypes (Journal of the Institute of Agriculture and Animal Science, 2025)
Genetic diversity is important for effective selection and genetic improvement in breeding programs. A study was conducted at Rampur, Chitwan, to study genetic parameters and the association between yield and yield-attributing traits. Thirty-six wheat genotypes were evaluated in an alpha lattice design with two replications. Effective tillers showed the highest genotypic coefficient of variation (GCV) (25.87%) and phenotypic coefficient of variation (27.61%). The difference between PCV and GCV was minimal for the studied traits. Grain yield recorded the highest broad-sense heritability (95%). Grain yield was positively correlated with harvest index, flag leaf area, plant height, and biological yield at both the genotypic and phenotypic levels (p < 0.05). Future breeding programs should prioritize these traits to improve wheat yield potential.